Pillars of stone or pillars of sand? An analysis of sustainability discourse in U.S. cities - Means, Morgann K. R., author; Opp, Susan, advisor; Duffy, Robert, committee member; McIvor, David, committee member; Carcasson, Martín, committee member (Colorado State University. Libraries, 2023)
Sustainability has emerged as a common governance paradigm in the United States, supplanting traditional top-down command-and-control regulations with a policy approach characterized by decentralization, municipal innovation, and the goal of ensuring that economic, environmental, and social systems function symbiotically. With institutional gridlock preventing comprehensive policy change at the national level coupled with state-by-state disparities in addressing environmental concerns, cities currently operate at the forefront of the sustainability movement. City governments have taken up the task of translating the broad precepts of sustainability into concrete policy decisions and planning trajectories. Despite its widespread adoption, the sustainability concept is as elusive as it is pervasive. While numerous cities throughout the United States have embraced sustainability as a guiding paradigm, the concept lacks an agreed-upon meaning and clear standards for practice. The recent rise of cities at the center of sustainability governance opens up numerous questions about how city officials navigate the definitional ambiguity of sustainability and integrate the core tenets of the concept into their planning frameworks. This dissertation contributes to a broader understanding of sustainable cities in the United States by analyzing three distinct, yet interrelated, aspects of municipal sustainability governance. First, through a content analysis of 200 U.S. cities, Chapter Two paints a picture of how cities conceptualize sustainability and the various factors (such as municipal demographics, structure of government, etc.) that correlate with a city's tendency to prioritize certain aspects of sustainability while deemphasizing others. Chapter Three builds upon this analysis by exploring the meaning of sustainability in disaster-vulnerable cities. Through both quantitative analysis and qualitative interview data, the chapter analyzes the nuances of policy change, issue definition, and the focal power of natural disasters in the sustainability domain. Chapter Four uses data from interviews conducted with city officials to examine the role of citizen participation in structuring the meaning of sustainability and the policy goals that cities incorporate under the sustainability umbrella. The core ideas from each of these chapters are discussed holistically in Chapter Five, which identifies how the findings from this dissertation provide empirical support for certain theories and assumptions related to sustainable cities, while challenging others. Taken as a whole, this dissertation finds significant variance in how cities conceptualize sustainability, shedding light on the contested meaning of the term. While the sustainability paradigm is often touted for its capacity to reduce tradeoffs between environmental protection, economic development, and social equity and to bring these three systems into a productive balance, this research shows that the meaning of sustainability is constructed situationally and that cities often prioritize only one or two pillars of the concept. Each chapter also sheds light on the nuances of issue definition and policy change in sustainable cities, including the catalytic impacts of natural disasters and the role that citizen participation plays in shaping cities' unique conceptualization of sustainability.
Keywords: focusing events; sustainability; citizen participation; sustainable cities; natural disasters